The Role Of Owner's Accounting Knowledge In Accounting Information Systems On Micro Small And Medium Enterprises - Indriyani Amellia Lestari (Universitas Muhammadiyah Jakarta, 2022)
Micro, Small and Medium Enterprises is the most important in the Indonesian economy. Based on data from the State Minister for Cooperatives Small and Medium Enterprises, the number of SME currently reaches 64.2 million with a contribution to GDP of 61.07% or 8,573.89 trillion rupiah. The contribution of MSMEs to the Indonesian economy that’s 97% of the total workforce and can collect up to 60.4% of the total investment. However, the high number of SME in Indonesian is also inseparable from the challenge that many MSMEs in Indonesia, especially in Cirebon Sindanglaut, still do not implement accounting information systems properly. This is because the owner's accounting knowledge is still lacking and the accounting information system is not used. So that the performance of MSMEs is also limited. The purpose of this study was to find out how much significant influence there is between the owner's accounting knowledge and the use of accounting information systems on the performance of an MSMEs especially in the Sindanglaut area of Cirebon. This research method uses quantitative methods and the data obtained is by conducting surveys and observations of SME in the Sindanglaut area, especially of MSMEs Alfiya Frozenfood. This study uses a test with multiple linear regression analysis with the result that the use of information systems (X1) and the owner's accounting knowledge (X2) has a significant effect of 99% on performance in a Micro, Small and Medium Enterprises.